1996
DOI: 10.1001/archpsyc.1996.01830070065010
|View full text |Cite
|
Sign up to set email alerts
|

Brain Anatomic Magnetic Resonance Imaging in Childhood-Onset Schizophrenia

Abstract: Brain anatomic abnormalities in childhood-onset schizophrenia are similar to those reported for adult populations, indicating overall continuity between these rare childhood cases and the adult schizophrenia populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(95 citation statements)
references
References 66 publications
9
85
1
Order By: Relevance
“…Indeed, individuals with ADHD (Trommer et al 1991;Barkley 1997;Casey et al 1997a) or schizophrenia (Braff 1993;Asarnow et al 1995) have difficulty regulating and suppressing inappropriate thoughts and actions. Furthermore, these disorders, as well as drug addiction, involve deficits in cognitive control and have been shown to involve the PFC (Lou et al 1989;Castellanos et al 1994Castellanos et al , 1996Fraizier et al 1996;Casey et al 2002;Cardinal et al 2004;Feil et al 2010;Goldstein et al 2011). An interesting hypothesis is that dysregulation of the developmental events leading to functional maturation of the PFC may contribute to or trigger the onset of ADHD and schizophrenia (Woo and Crowell 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, individuals with ADHD (Trommer et al 1991;Barkley 1997;Casey et al 1997a) or schizophrenia (Braff 1993;Asarnow et al 1995) have difficulty regulating and suppressing inappropriate thoughts and actions. Furthermore, these disorders, as well as drug addiction, involve deficits in cognitive control and have been shown to involve the PFC (Lou et al 1989;Castellanos et al 1994Castellanos et al , 1996Fraizier et al 1996;Casey et al 2002;Cardinal et al 2004;Feil et al 2010;Goldstein et al 2011). An interesting hypothesis is that dysregulation of the developmental events leading to functional maturation of the PFC may contribute to or trigger the onset of ADHD and schizophrenia (Woo and Crowell 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is predicated on the belief that studying first episode patients obviates confounds such as medication, chronicity of illness, and progressive changes. Research interest in childhood schizophrenia (Frazier et al, 1996(Frazier et al, , 1997Rapoport et al, 1997;Yeo et al, 1997) and adolescent schizophrenia (Dasari et al, 1999;James et al, 1999;Friedman et al, 1999) is also increasing. While these groups are not representative of the schizophrenia population and therefore may not be generalizable, they nonetheless offer important insights into the course of the illness and in change in brain morphology.…”
Section: The Issuesmentioning
confidence: 99%
“…Neuroimaging studies of adult-onset schizophrenia have consistently reported increased lateral ventricular volume [35], reduced gray and white matter volumes [36][37][38], particularly in the prefrontal region [39], and a reduction in thalamic size [40]. Similarly, imaging studies on early-onset cases have reported enlarged ventricular size, lower regional gray matter volumes (e.g., prefrontal cortex and cerebellum), white matter abnormalities [41], increased basal ganglia volume [14,17,42] and reduced volume of the thalamus [9,43], cerebellum [42] and anterior cingulated gyrus [44]. Adult-onset studies have also reported hippo campal volume reduction [45].…”
Section: "The Neurodevelopmental Hypothesis Proposesmentioning
confidence: 97%
“…EOS lies at one end of the continuum of disease severity and genetic liability [7]. Early-onset cases show clinical, cognitive, genetic and neurobiologic continuity with adult-onset schizophrenia [7][8][9], albeit with enduring clinical morbidity and psychosocial disability [10]. Thus, the study of this enriched population is likely to provide important pointers to the neurodevelopmental origins and pathophysiological mechanisms of schizophrenia.…”
mentioning
confidence: 99%